PENGUJIAN PRAKTIKALITAS MODEL KEGIATAN EKSTRAKURIKULER PENDIDIKAN AGAMA ISLAM BERBASIS PENDEKATAN SAINTIFIK UNTUK SEKOLAH DASAR - Yarhamna Yarhamna; Annisaul Khairat; Iskandar Fuaddin; Fismal Fismal (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2019)
The objectives of this study to develop a model of religious extracurricular activities and produce a model book of the religious extracurricular activities based on a practical scientific approach. The research method used was a Research and Development (R and D) with the Borg and Gall model. The data collection tool was observation sheet. Then the data were analyzed quantitatively by using Aiken V index calculation, if the index is 0.0 <V ≤ 0.200 it is said that the validity is very low, if 0.200 <V ≤ 0.400 is said to be low, 0.400 <V 600 0.600 is said to be practical, 0.600 <V 800 0.800 is practical, 0800 < V ≤ 1.00 can be said to be very practical. The results of the practicality test of the religious extracurricular activity model based on the scientific approach obtained an average of 0.85 in the very practical category after field trials were carried out, so that the model of religious extracurricular activities was feasible to use.